Demographic differences in willingness to share electronic health records in the All of Us Research Program. (26th April 2022) - Joseph, Christine L M; Tang, Amy; Chesla, David W; Epstein, Mara M; Pawloski, Pamala A; Stevens, Alan B; Waring, Stephen C; Ahmedani, Brian K; Johnson, Christine C; Peltz-Rauchman, Cathryn D
Abstract: Objective: Participant willingness to share electronic health record (EHR) information is central to success of the National Institutes of Health All of Us Research Program (AoURP). We describe the demographic characteristics of participants who decline access to their EHR data. Materials and Methods: We included participants enrolling in AoURP between June 6, 2017 and December 31, 2019 through the Trans-American Consortium for the Health Care Systems Research Network (TACH). TACH is a consortium of health care systems spanning 6 states, and an AoURP research partner. Results: We analyzed data for 25 852 participants (89.3% of those enrolled). Mean age = 52.0 years (SD 16.8), with 66.5% White, 18.7% Black/African American, 7.7% Hispanic, 32.5% female, and 76% with >a high school diploma. Overall, 2.3% of participants declined to share access to their EHR data (range across TACH sites = 1.3% to 3.5%). Younger age, female sex, and education >high school were significantly associated with decline to share EHR data, odds ratio (95% confidence interval) = 1.26 (1.19–1.33), 1.74 (1.42–2.14), and 2.44 (1.86–3.21), respectively. Results were similar when several sensitivity analyses were performed. Discussion: AoURP seeks a dataset reflecting our nation's diversity in all aspects of participation. Those under-represented in biomedical research may be reluctant to share access to their EHR data. Conclusion: In our data, race and ethnicity were not independently related to participant decision to decline access to their EHR information. Results suggest that the value of the AoURP dataset is unlikely to be constrained by the size or the racial/ethnic composition of this subgroup.